Cover Picture: A Cactus‐Derived Toxin‐Like Cystine Knot Peptide with Selective Antimicrobial Activity (ChemBioChem 7/2015). Issue 7 (4th May 2015) - Aboye, Teshome L.; Strömstedt, Adam A.; Gunasekera, Sunithi; Bruhn, Jan G.; El‐Seedi, Hesham; Rosengren, K. Johan; Göransson, Ulf
<x xml:space="preserve">Abstract</x> The cover picture shows the solution structure of the peptide Ep‐AMP1 and the source of the peptide, the San Pedro cactus (Echinopsis pachanoi). Ep‐AMP1 is the first cystine knot peptide isolated from the plant family of Cactaceae. Sequence homology places this peptide in the family of C6‐type of antimicrobial peptides, but the three dimensional structure is highly similar to that of a peptide‐based spider neurotoxin. Ep‐AMP1 displays potent antimicrobial and membrane permeabilising activity. The article by U. Göransson et al. (see the full paper on p. 1068 ff.) reports the discovery, sequencing, chemical synthesis, structure determination and bioactivity of this peptide. Photo of E. pachanoi by Matthias Uhlig, Uhlig Kakteen.